Taxa dedicated to Alberto C. Riccardi - Macellari, Carlos E. (2012)
Dr. Alberto Riccardi has greatly impacted in the advance of palaeontological and geological knowledge in several areas of the world, particularly in LatinAmerica. As a token of appreciation to his outstanding career, contributions, and positive influence, he has been recognized in several instances with the dedication of taxa bearing his name. His former mentor, several of his former students, and colleagues are among the people that have dedicated scientific names to him. This brief contribution summarizes the taxa and the circumstances related to each genus and species dedicated to Dr. Riccardi of which the authors are aware.